Chester Raccoon and the big bad bully - Penn, Audrey, 1947-; Gibson, Barbara (Terre Haute, IN : Tanglewood Press, 2008)
When Chester tells his mother about the school bully, she asks him to gather his friends to hear a story about getting along with people who are prickly.
Keywords: Bullies -- Fiction; Conflict management -- Fiction; Nonviolence -- Fiction; Procyon -- Fiction; Raccoon -- Fiction; Animals -- Fiction